The Influence of Maternal Nutrition Consumption Level During Breastfeeding on Breast Milk Macronutrient Component and Infant’s Weight - Nina Hidayatunnikmah; Roedi Irawan; Budi Prasety (Health Notions, 2018)
Fine intake of maternal nutrient consumption was important for the health of mother and the baby. There were previous researches explained that the maternal nutrition consumption level during breastfeeding could influence breast milk macronutrient component. Breast milk macronutrient components can support infants growth process. Analyzing the influence of maternal nutrient consumption level during breastfeeding on breast milk macronutrient component and infant weight. The information regarding maternal nutrition consumption level during breastfeeding was obtained by using food recall for 24 hours in two days. Furthermore, infant birth weight was measured by using Z-score value, while macronutrient component of breast milk by using MIRIS tool with 60 breastfeeding mother as the sample. Statistic test used categorical regression (CATREG). Based on 60 samples, it was showed that average carbohydrate consumption level 384.3 ± 53.3 gram, protein consumption level 81.5 ± 11.9 gram, and fat consumption level 85.1 ± 15.5 gram. There carbohydrate components of milk of 4.7 ± 0.6 gr / dl, protein components of breast milk 2.4 ± 2.2 gr / dl, and fat component of breast milk 3.6 ± 1.4 gr / dl. Fat consumption levels negative influenced towards the carbohydrate components of breast milk (B = -0.356, p = 0.001) and the level of protein and fat consumption level took a positive effect on fat components of breast mik (B = 0218 and B = 0.576, p = 0.029 and p = 0.000). Meanwhile, protein and fat components of breast milk were positive effect on infant weight (B = 0.323 and B = 0.253; p = 0.037 and p = 0.045). Fine fat consumption could produce a good fat componen of breast milk. In addition, protein and fat component of breast milk give impact on infant weight. Keywords: Maternal nutrition, Consumption level, Breastmilk, Macronutrient, Infant’s weight